2010
DOI: 10.2139/ssrn.1564746
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Forecasting of Noncausal Autoregressive Time Series

Abstract: In this paper, we propose a simulation-based method for computing point and density forecasts for univariate noncausal and non-Gaussian autoregressive processes. Numerical methods are needed to forecast such time series because the prediction problem is generally nonlinear and no analytic solution is therefore available. According to a limited simulation experiment, the use of a correct noncausal model can lead to substantial gains in forecast accuracy over the corresponding causal model. An empirical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…where b f and b b are the ML estimates, and E t t+1 can be computed as a forecast from the estimated AR(r, s) as shown by Lanne et al (2010). Neither the marginal cost variable x t nor the coe¢ cient as such are not, of course, identi…able, but the time series of x t are informative about the properties of the implied drivers of the in ‡ation series.…”
Section: What Drives In ‡Ation?mentioning
confidence: 99%
“…where b f and b b are the ML estimates, and E t t+1 can be computed as a forecast from the estimated AR(r, s) as shown by Lanne et al (2010). Neither the marginal cost variable x t nor the coe¢ cient as such are not, of course, identi…able, but the time series of x t are informative about the properties of the implied drivers of the in ‡ation series.…”
Section: What Drives In ‡Ation?mentioning
confidence: 99%
“…Therefore, following Lanne and Saikkonen (2008), we specify Student's t-distribution for t . In addition to these authors, also Lanne et al (2009Lanne et al ( , 2010 have shown this distribution to …t U.S. in ‡ation series well.…”
mentioning
confidence: 73%
“…In addition to the univariate causal and noncausal AR models, random walk forecasts of Atkeson and Ohanian (2001) and moving average forecasts are consid- we only consider iterated multistep forecasts that SW found quantitatively quite similar to their direct forecasts. Lanne and Saikkonen (2008) propose a model selection procedure that was employed in forecasting by Lanne et al (2010). However, in this paper all noncausal forecasts are based on the recursively estimated …xed AR(0,4) model that should be adequate for quarterly data.…”
Section: Forecast Resultsmentioning
confidence: 99%
See 2 more Smart Citations